Mesolithic Eel-Fishing at Bjørnsholm, Denmark, Spiced with Exotic Species - Bødker, Inge (Journal of Danish Archaeology, 1991)
Mesolithic Eel-Fishing at Bjørnsholm, Denmark, Spiced with Exotic Species